Redskins : Insult and Brand - King, C. Richard, 1968- (Book collections on Project MUSE., 2016)
"Redskins: Insult and Brand examines how the ongoing struggle over the team name raises important questions about how white Americans perceive American Indians, about the cultural power of consumer brands, and about continuing obstacles to inclusion and equality. C. Richard King examines the history of the team's name, the evolution of the term "redskin," and the various ways in which people both support and oppose its use today. King's hard-hitting approach to the team's logo and mascot exposes the disturbing history of a moniker's association with the NFL--a multibillion-dollar entity that accepts public funds--as well as popular attitudes toward Native Americans today"--Provided by publisher